Unlocking Maternal Potential: A Pathway Analysis of Information, Motivation, and Skills Application on Child Development in Sleman, Yogyakarta, Indonesia - Firdaus, Anisah; Prasetya, Hanung; Murti, Bhisma (Journal of Maternal and Child Health, 2025)
Background: Toddlers (ages 0-5 years) are a golden period in human development. In this period, there is rapid development in various aspects, such as physical, cognitive, language, social, and emotional. Mother's behavior in providing stimulation and care can affect the development of toddlers. This study focuses on the analysis of the influence of the Information Motivation Behavior Skill Model application on maternal behavior for the development of toddlers. Subjects and Method: This study is a cross-sectional study conducted at 25 integrated health posts in Sleman Regency, Yogyakarta from April to May 2024. The sample consisted of 200 mothers of toddlers aged 24-60 months who were selected using the simple random sampling method. The dependent variable in this study was maternal behavior in nurturing the development of toddlers. The independent variables were maternal information/knowledge, maternal motivation, maternal behavior skills, and maternal income. Data collection was carried out by interviews and questionnaires. The data analysis was using path analysis. Results: The results of path analysis show that maternal behavior in nurturing the development of toddlers is positively related to good behavioral skills. (OR= 1.22; CI 95%= 0.70-0.80; p< 0.001). Maternal behavioral skills are influenced by information (OR= 1.35; CI 95%= 0.899-1.90; p<0.001) and motivation (OR= 1.36; CI 95%= 0.82-1.89; p<0.001).  The path analysis model showed good fit (p= 0.134 (>0.05); RSMEA= 0.06 (<0.08); CFI= 0.98 (>0.90); TLI= 0.97).    Conclusion: Maternal behavior in nurturing toddler development is directly influenced by maternal behavioral skills, maternal information/knowledge, maternal income. Mother's behavior in nurturing toddler development is indirectly influenced by information on maternal behavior through maternal behavior skills and maternal motivation towards maternal behavior through maternal behavior skills. Thus, the Information Motivation Behavior Skill Model can be used to improve maternal behavior in nurturing toddler development.